Income and child well-being - Duncan, Greg J. (Economic and Social Research Institute, 2006)
My topic this afternoon is the link between family income and the well-being of children. While it is easy to document the better health and higher achievement of children who have grown up in richer as opposed to poorer families, it is much harder to isolate the causal impact of income itself. Children growing up in higher income families are advantaged in many other ways, including having parents who have completed more formal schooling and are embedded in higher-status social networks, and whose genetic endowments may provide cognitive and health-related advantages. The question I seek to answer concerns the impact of income itself and takes the form of a policy thought experiment: by how much would we expect a child’s well-being to improve if that child’s family were unexpectedly given more income through, say, a more generous child allowance? In attempting to answer this question I will first discuss relevant models of child development from economics and developmental psychology and then document some of the differences in well-being between high and low income children. I will then review some of the empirical studies of the links between income and child achievement. In my review I will begin with cross-sectional evidence, move next to longitudinal studies and then consider some recent innovative studies that use natural and random-assignment experiments and instrumental variables methods. I will conclude with some thoughts about the policy implications of the results from these studies.